Integrating XSL-FO into Web-Based Applications JavaMail and PDF report creation. - Ng, Adelene
This article demonstrates how we can integrate XSL-FO, XSLT and JavaMail into our existing web-based applications. I show you how we can generate PDF reports for an application through the use of XSLT and XSL-FO embedded within the Java application. I also illustrate how the generated PDF file can be sent as an e-mail attachment using JavaMail.